Lanthanide rare earth oxide thin film as an alternative gate oxide - Goh, K.H.; Haseeb, A.S. Md. Abdul; Wong, Y.H. (Elsevier, 2017)
An ultrathin gate oxide is needed for future nanoscale technology due to the density of integrated circuits will increase exponentially every two to three years as predicted by Moore's Law. Some problems were occurred in conventional silicon dioxide gate oxide during applications such as high leakage current density, low reliability issues, and undesirable power dissipation. Lanthanide rare earth oxides was attracted as one of potential candidates to replace conventional silicon dioxide due to their superior properties. Each rare earth oxides in lanthanide group was reviewed and discussed in terms of physical, chemical, and electrical properties and also its common deposition methods. Sm2O3 is one of the promising candidate materials among rare earth oxides because of some outstanding properties such as high κ (7–22), high breakdown electric field (5–7 MV cm-1), relatively large bandgap (4.33 eV), low leakage current, large conduction offset with Si, high thermal stability, small frequency dispersion, low trapping rate, and low hygroscopic characteristic. The literatures of Sm2O3 was paid particular attention in the last section. The previous deposition methods of the Sm2O3 as gate oxide were reviewed and compared.